How firm characteristics increase the explanatory power of the earnings function: Gender wage inequality in Malaysia Puvanesvaran A/L Sanjivee - Sanjivee, Puvanesvaran (2015)

(untitled)
This study investigates the role firm characteristics plays in explaining gender wage inequality. Prior research has mainly explored two strands to explain inequality in the labour market. The first, carried out primarily by sociologists and feminists, attempts to explain gender discrimination by showing that females are segregated into lower paying occupations while higher paying occupations are being dominated by males. This strand usually does not consider the workers’ endowment. The second strand, mainly by econo-mists, measures discrimination based on wage differentials after accounting for workers endowment. Recent evidence worldwide shows that females are outstripping males in the pursuit of higher education, suggesting that females find greater opportunities in high paying occupations. Hence, it becomes important to relook segregation using more current data. While studies have shown that firm characteristics do play a significant role in determining workers’ wages, researchers generally disregard these variables in their analysis thereby resulting in a lack of studies that attempt to show how individual firm-related characteristics can affect wage inequality. Besides relooking at the distribution of occupations, this study also looks at the impact of the firm-related characteristics on gender wage inequality, and attempts to asses if studies that do not include firm-related variables in the analysis possibly suffer from bias as a result of this exclusion. The research framework blends the relevant literatures to create an empirically testable methodology for investigating the roles played by occupational segregation, worker endowment and various firm characteristic in explaining gender wage inequality. The analysis is conducted on a large primary employer-employee linked dataset from Malaysia. iii The results, firstly, indicate that females in the dataset have a superior occupational distri-bution in Malaysia which is reflective of their superior educational attainment. Secondly, the inclusion of firm characteristics in the Mincerian earnings equation provided a different set of coefficients for the human capital variables as compared to when only the latter were used as the explanatory variables. With the inclusion of the firm-related variables, the coefficients of the human capital variables became significantly smaller. This suggests that the widely used form of Mincer’s equation is incorrectly specified for it over-estimates the coefficients to compensate for missing variables. The study finds that gender composition at a workplace affects female and male workers’ wages differently. It also finds that while the larger firms generally offer higher wages, the gender wage differentials are also larger. The greatest differentials are among firms with foreign equity. Also, more than half of the employees in the firms with foreign sharehold-ing are female. While it may be argued that the results suggest that large firms and FDI recipient firms may be more discriminatory against females, a significant portion of these differentials can be explained by analysing the firm and industry specific human capital of workers. Larger firms and FDI recipient firms have higher capital-labour ratios, and as such demand more skilled workers. Female workers should develop and upgrade their firm or industry specific skills to reduce wage differentials.